Bamboo aggregate concrete and preparation method thereof

By replacing the gravel and cement in traditional concrete with bamboo aggregate and bamboo leaf ash, an environmentally friendly and high-performance bamboo aggregate concrete was prepared, which solved the negative impact of traditional concrete processes on the environment and resources.

CN119822724APending Publication Date: 2025-04-15CHONGQING THREE GORGES UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411995400.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Environmental and resource problems caused by traditional cement concrete preparation processes include damage to the natural environment by gravel mining and high energy consumption by cement production.

Method used

Bamboo aggregate is used to replace traditional gravel, and bamboo leaf ash is partially replaced by cement, combining sand, water, water reducer, gas induction agent, coagulant, filler and antichloride ion additives and other raw materials to prepare bamboo aggregate concrete.

Benefits of technology

Effectively utilize bamboo aggregate resources, reduce dependence on gravel and cement, reduce environmental damage and energy consumption, and improve the physical and mechanical properties and durability of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822724A_ABST
    Figure CN119822724A_ABST
Patent Text Reader

Abstract

The invention discloses bamboo aggregate concrete, which is prepared from the following raw materials in parts by weight: 20 to 30 parts of bamboo aggregate, 20 to 30 parts of cement, 5 to 10 parts of bamboo leaf ash, 35 to 40 parts of sand, 10 to 15 parts of water, 0.5 to 1.5 parts of water reducing agents, 0.01 to 0.03 part of air entraining agents, 2.5 to 4.0 parts of coagulation accelerators, 0.2 to 1.2 parts of filling materials and 0 to 1.5 parts of chloride ion resisting additives, the invention also discloses a preparation method of the bamboo aggregate concrete. The preparation method comprises the following steps: preparing the bamboo aggregate; preparing bamboo leaf ash; the bamboo aggregate, the sand, the bamboo leaf ash, the cement, the water, the water reducing agent, the air entraining agent and the coagulant are uniformly mixed, the preparation process is simple, efficient and pollution-free, not only is efficient utilization of bamboo aggregate resources realized, but also the prepared bamboo aggregate concrete has excellent physical and mechanical properties, meanwhile, the burden on the environment is remarkably reduced, and the production cost is reduced. And a green, sustainable and high-performance novel building material is provided for the building industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to bamboo aggregate concrete and a preparation method thereof. Background Art

[0002] Against the backdrop of the rapid development of the global construction industry, the demand for concrete, as an indispensable key material for infrastructure construction, continues to rise. However, in the traditional cement concrete preparation process, crushed stone is generally used as coarse aggregate and cement is used as the dominant cementitious material. While supporting the rapid development of the construction industry, this model has also led to a series of severe environmental and resource problems. From an ecological perspective, the large-scale mining of crushed stone has caused irreversible damage to the natural environment. According to statistics, the area of ​​vegetation damage caused by crushed stone mining is as high as millions of hectares worldwide each year, which not only leads to serious soil erosion, resulting in the loss of hundreds of millions of tons of water and soil resources, but also destroys the ecological balance. In particular, in some mountainous areas, excessive mining of crushed stone has caused a sharp decline in mountain vegetation coverage, a significant increase in the sand content of surrounding rivers, and a serious threat to the stability of the ecosystem. Geological disasters such as mudslides and landslides occur frequently, posing a huge threat to the safety of life and property of surrounding residents and regional ecological stability. At the resource and energy level, the cement production process also places a heavy burden on the environment; for every ton of cement produced, about 1.5 tons of non-renewable mineral resources such as limestone are consumed, and nearly 1 ton of carbon dioxide is emitted simultaneously, which makes the cement industry account for a very high proportion of the global carbon emissions; according to statistics, the cement industry's carbon emissions have long been at the forefront of the industrial sector, becoming one of the key factors driving global warming. At the same time, cement production has also accelerated the depletion of non-renewable resources and exacerbated the energy crisis.

[0003] Although various paths for improving traditional concrete have been explored in this field, these methods all have obvious limitations, such as using lightweight concrete to replace traditional concrete, and using expanded clay to replace crushed stone. However, the production of expanded clay relies on clay, and high-temperature firing consumes huge amounts of energy, and clay resources are scarce. Alternatively, industrial waste residues may be added for resource utilization, but due to large fluctuations in the composition of the waste residues, the quality of the concrete may vary, making it difficult to meet the standards for stability and durability of building structures. Alternatively, foamed concrete may be used, which has the advantages of light weight, environmental protection, and easy construction, but has quality problems such as low compressive strength and prone to cracking.

[0004] Therefore, in view of the current severe ecological environment and resource and energy situation, it is particularly urgent to develop a new type of concrete material that is both environmentally friendly and has stable performance. my country has abundant bamboo aggregate resources, and bamboo has a short growth cycle and strong renewability, which provides new ideas and possibilities for using bamboo aggregate to replace gravel and cement in traditional concrete, and is expected to break through the bottleneck of traditional concrete preparation technology and open up a new path for the sustainable development of building materials. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a bamboo aggregate concrete and a preparation method thereof, using bamboo aggregate to replace traditional crushed stone as coarse aggregate, constructing a bamboo aggregate bamboo leaf ash concrete system, so as to solve the environmental and resource problems caused by the traditional cement concrete preparation process.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0007] A bamboo aggregate concrete comprises the following raw materials in parts by weight: 20-30 parts of bamboo aggregate, 20-30 parts of cement, 5-10 parts of bamboo leaf ash, 35-40 parts of sand, 10-15 parts of water, 0.5-1.5 parts of water reducer, 0.01-0.03 parts of air entraining agent, 2.5-4.0 parts of coagulant, 0.2-1.2 parts of filler and 0-1.5 parts of chloride ion resistance additive.

[0008] According to the above technical means, my country has abundant bamboo aggregate resources and is widely distributed. Bamboo has the characteristics of short growth cycle, excellent mechanical properties and strong carbon absorption capacity, and is a renewable resource; bamboo aggregate can not only realize the renewable utilization of resources, but also reduce the consumption of resources and energy; bamboo leaf ash not only improves the impermeability and durability of concrete, but also reduces the amount of cement and improves resource utilization; water reducer is a concrete admixture that can reduce the amount of mixing water while maintaining the slump of concrete. It is mainly used to improve the fluidity of concrete mixtures, such as lignin sulfonate, naphthalene sulfonate, melamine series, aminosulfonate series high efficiency, fatty acid series high efficiency, powdered polycarboxylate, etc.; air entraining agent, also known as air entraining agent, is a hydrophobic Surfactants, which are dissolved in water and added to concrete, can produce a large number of tiny bubbles during the mixing process to block water seepage channels and improve the concrete's frost resistance, salt resistance, impermeability and sulfate corrosion resistance, such as rosin resins, alkylbenzene sulfonates, etc.; accelerators are used to promote the coagulation and hardening of concrete, improve the strength and durability of concrete, shorten the setting time of concrete, and speed up the construction progress. The most common accelerators are silicate and calcium-based accelerators; fillers added to concrete can not only reduce the porosity inside the concrete, thereby reducing the diffusion rate of chloride ions, but also reduce the amount of cement used and improve the resource utilization of industrial waste residues; adding anti-chloride ion additives to concrete can improve its ability to resist chloride ion penetration;

[0009] The present invention adopts bamboo aggregate to replace crushed stone, bamboo leaf ash to partially replace cement, and combines sand, water, water reducer, air entraining agent, accelerator, filler and anti-chloride ion additive and other raw materials to form bamboo aggregate concrete, which can not only effectively utilize my country's abundant bamboo aggregate resources and realize the renewable utilization of resources, but also reduce the dependence on crushed stone and cement compared with traditional cement concrete, thereby reducing the environmental damage and energy consumption caused by the mining and production of these materials, and opens up an innovative and environmentally friendly new way for the green and sustainable development of building materials.

[0010] Furthermore, the filler is one or more of polyhydroxyalkanoate, ground slag powder and silica fume.

[0011] According to the above technical means, polyhydroxyalkanoates are added to concrete, and their particles can fill the pores of concrete to reduce the porosity. At the same time, the active groups on their surface react chemically with functional groups such as hydroxyl groups on the surface of cement particles to form a strong interface bond, thereby improving the mechanical properties of concrete such as compressive strength, flexural strength and durability; ground slag powder can play a filling role of finer particles in concrete because its fineness is finer than cement particles, thereby improving the pore structure of concrete, reducing porosity and reducing the size of the maximum pore size; silica fume is solid particles collected after oxidation and condensation of silicon vapor discharged from the flue during industrial smelting of ferrosilicon or silicon alloys. It has high activity, and fine particles can fill the pores of concrete, thereby reducing the pores of concrete. Silica powder can also bind to alkali in concrete to reduce the alkali content of concrete, thereby reducing the risk of acid and alkali corrosion and improving the acid and alkali resistance of concrete.

[0012] Furthermore, the chloride ion resistance additive is one or more of potassium chloride, sodium potassium chloride and copper chloride.

[0013] According to the above technical means, in coastal areas or road environments where deicing salt is often used, the chloride ion content of the road surface is high, and the chloride ions will penetrate into the concrete, not only interacting with the reactants inside the cement, causing the concrete to expand and increase in volume, thereby causing the concrete to crack, but also destroying the concrete's own resistance to chemical corrosion, reducing the concrete's wear resistance and strength;

[0014] Potassium chloride and sodium potassium chloride can provide chloride ions and form chelates with metal ions (such as calcium ions, magnesium ions, etc.) in concrete, thereby reducing the invasion of external chloride ions and improving the concrete's resistance to chloride ions. Cupric chloride can not only provide chloride ions to improve the concrete's resistance to chloride ions, but also serve as an effective ingredient in fungicides or insecticides. When used in bamboo aggregates, it can prevent insects and corrosion. The addition of copper oxide is an inorganic substance that can be absorbed by bamboo to form a smooth and dense surface protective film to prevent moisture intrusion, which has the effect of reducing the moisture of bamboo aggregates.

[0015] A method for preparing the bamboo aggregate concrete is characterized by comprising the following steps:

[0016] S1. Preparation of bamboo aggregate: fresh bamboo is cut into standard lengths, impurities are removed, and the bamboo aggregate particles are crushed. The bamboo aggregate particles are first soaked by vacuum negative pressure assisted soaking technology, drained, and then the drained bamboo aggregate particles are steamed by a steam treatment kettle, and dried to obtain bamboo aggregate;

[0017] S2. Preparation of bamboo leaf ash: pyrolysis, cooling and grinding of fresh bamboo leaves to obtain bamboo leaf ash;

[0018] S3, first take the bamboo aggregate prepared in step S1 and sand, mix them, stir them evenly, and obtain mixture one; then take the bamboo leaf ash and cement prepared in step S2, add them to mixture one, stir them evenly, and obtain mixture two; finally, take water, water reducing agent, air entraining agent, coagulant, filler and anti-chloride ion additive and add them to mixture two, stir them evenly, and obtain bamboo aggregate concrete.

[0019] According to the above technical means, fresh bamboo is prepared into bamboo aggregate by means of removing impurities, crushing, soaking, steam treatment, etc., and fresh bamboo leaves are pyrolyzed and ground to obtain bamboo leaf ash. Then, through optimal proportioning and mixing process, bamboo aggregate, bamboo leaf ash, sand, cement, water, water reducer, air entraining agent, coagulant, filler and anti-chloride ion additive are fully integrated. The preparation process is simple, efficient and pollution-free, which not only realizes the efficient utilization of bamboo aggregate resources, but also the prepared bamboo aggregate concrete has excellent physical and mechanical properties, while significantly reducing the burden on the environment, providing the construction industry with a green, sustainable and high-performance new building material.

[0020] Furthermore, in step S1, the fresh bamboo is 3-5 years old and has a breast diameter of 8-12 cm; the standard length is 1 m-1.5 m; and the particle size of the bamboo aggregate particles is 5 mm-20 mm.

[0021] According to the above technical means, by selecting 3-5 year old fresh bamboo with a breast diameter of 8-12cm, the bamboo fiber cell wall thickness at this growth stage is uniform and the degree of lignification is appropriate, which lays the foundation for the preparation of high-performance bamboo aggregate and ensures the quality and strength of the bamboo aggregate. After cutting it into a standard length of 1m-1.5m, it is removed from impurities and crushed into bamboo aggregate particles with a particle size of 5mm-20mm. This not only improves the uniformity and applicability of the bamboo aggregate, but also effectively improves the strength and durability of bamboo aggregate concrete, further enhancing its application potential as a green building material in the construction field.

[0022] Furthermore, the specific steps of soaking the bamboo aggregate particles using the vacuum negative pressure assisted soaking technology in step S1 are as follows:

[0023] The crushed bamboo aggregate particles are first treated in a negative pressure environment for 30 minutes, and then soaked in a normal pressure environment for 12-15 hours.

[0024] According to the above technical means, the vacuum negative pressure assisted immersion technology is used to treat the bamboo aggregate particles. By first treating them in a negative pressure environment for 30 minutes, a negative pressure state is formed inside the bamboo aggregate particles, which promotes the full expansion of the internal pores of the bamboo aggregate and constructs micro-channels that are conducive to the penetration of the soaking liquid. Then, the soaking liquid is added and soaked in a normal pressure environment for 12-15 hours, so that the soaking liquid can penetrate more deeply into the bamboo aggregate particles, effectively enhancing the wettability of the bamboo aggregate particles and the bonding strength with subsequent materials, thereby improving the overall strength and stability of the bamboo aggregate concrete, laying a solid foundation for the preparation of high-performance bamboo aggregate concrete.

[0025] Furthermore, the negative pressure is -0.08 MPa to -0.1 MPa.

[0026] According to the above technical means, the negative pressure is precisely controlled within the range of -0.08MPa to -0.1MPa, which can ensure that the bamboo aggregate particles reach the optimal negative pressure state during the vacuum negative pressure assisted immersion process. This not only promotes the soaking liquid to penetrate into the bamboo aggregate particles more fully and evenly, but also further optimizes the structural properties of the bamboo aggregate particles and improves the bonding strength between the bamboo aggregate and the concrete, providing a strong guarantee for the preparation of bamboo aggregate concrete with stable quality and excellent performance.

[0027] Furthermore, the steam treatment in step S1 is performed under a pressure of 0.3 MPa, a temperature of 130° C., and a time of 3.5 h.

[0028] According to the above technical means, by setting the steam treatment pressure of the steam treatment kettle to 0.3MPa, the temperature to 130℃, and the time to 3.5h, the bamboo aggregate particles can be efficiently pyrolyzed, which not only effectively removes part of the moisture and volatile substances in the bamboo aggregate, but also improves the density and stability of the bamboo aggregate, enhances the compatibility and adhesion between the bamboo aggregate particles and the concrete matrix, and provides key technical support for the preparation of high-strength and high-durability bamboo aggregate concrete.

[0029] Furthermore, the moisture content of the bamboo aggregate in step S1 is 12%-15%.

[0030] According to the above technical means, the moisture content of bamboo aggregate is precisely controlled within the range of 12%-15%, which can ensure that the bamboo aggregate particles maintain an appropriate moisture content in the subsequent concrete preparation process, which is not only conducive to the full mixing and uniform dispersion of bamboo aggregate particles with other raw materials such as cement and sand, but also can avoid the appearance of excessive free water in the concrete preparation process, thereby improving the working performance of bamboo aggregate concrete and the mechanical properties after hardening, providing an important guarantee for the preparation of bamboo aggregate concrete products with stable quality and excellent performance.

[0031] Furthermore, the pyrolysis temperature in step S2 is 400-600° C., and the pyrolysis time is 2-3 hours.

[0032] According to the above technical means, bamboo absorbs a large amount of silicon, aluminum and other elements from the soil during its growth. The pyrolysis temperature is set in the range of 400-600°C, and the pyrolysis time is controlled to 2-3h, which can ensure that the bamboo leaves are uniformly decomposed by heat, fully react and transform with oxygen, and efficiently decompose the organic matter in the bamboo leaves. At the same time, active aluminosilicates are enriched to form bamboo leaf ash rich in active aluminosilicate components. The silicon oxygen tetrahedron and aluminum oxygen octahedron structures of the active aluminosilicates are depolymerized and reorganized in the alkaline environment created by cement hydration to generate additional gel products to accurately fill the pores, enhance the density of the concrete, and promote the steady increase of the early strength. Therefore, the use of bamboo leaf ash in the present invention not only increases the cementitious properties of the concrete, but also improves the impermeability and durability of the concrete, providing strong technical support for the preparation of high-performance, environmentally friendly bamboo aggregate concrete.

[0033] Furthermore, the grinding fineness of the bamboo leaf ash in step S2 is 0.08-0.12 mm.

[0034] According to the above technical means, the grinding fineness of bamboo leaf ash is controlled within the range of 0.08-0.12mm, which can ensure that the bamboo leaf ash is evenly distributed in the bamboo aggregate concrete and fully reacts with other components such as cement and bamboo aggregate to form a more compact and stable concrete structure, thereby improving the density and strength of the concrete, and providing important technical guarantees for the preparation of high-performance, high-quality bamboo aggregate concrete products.

[0035] Furthermore, in step S3, the stirring speed of the mixture 1 is 25-30 r / min, and the stirring time is 2-3 min; the stirring speed of the mixture 2 is 35-40 r / min, and the stirring time is 1-2 min; the stirring speed of the mixture 3 is 45-50 r / min, and the stirring time is 3-5 min.

[0036] According to the above technical means, by accurately controlling the stirring speed and stirring time in different mixing stages, it is ensured that the components can be fully and evenly mixed, avoiding the performance degradation caused by uneven stirring, improving the production efficiency of bamboo aggregate concrete, and improving the physical and mechanical properties and durability of bamboo aggregate concrete, laying a solid foundation for the preparation of high-performance, high-quality bamboo aggregate concrete products.

[0037] Beneficial effects achieved by the present invention:

[0038] 1. The present invention adopts bamboo aggregate instead of crushed stone and bamboo leaf ash as gel material, which can reduce the amount of cement used, and combines sand, water, water reducer, air entraining agent and accelerator to form bamboo aggregate concrete, which can not only effectively utilize my country's abundant bamboo aggregate resources and realize the renewable utilization of resources, but also reduce the dependence on crushed stone and cement compared with traditional cement concrete, thereby reducing the environmental damage and energy consumption caused by the mining and production of these materials, and opening up an innovative and environmentally friendly new way for the green and sustainable development of building materials.

[0039] 2. Fresh bamboo is used to prepare bamboo aggregate through means of removing impurities, crushing, soaking, steam treatment, etc., and fresh bamboo leaves are pyrolyzed and ground to obtain bamboo leaf ash. After an optimal proportioning and mixing process, the bamboo aggregate, bamboo leaf ash, sand, cement, water, water reducer, air entraining agent, accelerator filler and anti-chloride ion additive are fully integrated. The preparation process is simple, efficient and pollution-free, which not only realizes the efficient utilization of bamboo aggregate resources, but also the prepared bamboo aggregate concrete has excellent physical and mechanical properties, while significantly reducing the burden on the environment, providing a green, sustainable and high-performance new building material for the construction industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 1 is a performance comparison chart of bamboo aggregate concrete in Examples 1-6 of the present invention. Specific embodiments

[0041] In order to better understand the technical solution, purpose and beneficial effects of the present invention, the present invention is further specifically described through the following examples, but it should not be understood as limiting the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above invention content are also considered to fall within the protection scope of the present invention. The experimental methods without specific conditions in the examples are usually carried out under conventional conditions or under the conditions recommended by the reagent manufacturer.

[0042] The invention uses non-destructive testing technologies such as ultrasonic flaw detectors to survey bamboo forests on site, and selects 3-5 year old fresh bamboos with a breast diameter of 8-12 cm as raw materials for bamboo aggregates and bamboo leaf ash according to the internal density uniformity and wave velocity propagation characteristics of bamboo aggregates.

[0043] Embodiment 1:

[0044] The preparation of bamboo aggregate concrete includes the following steps:

[0045] S1. Pretreatment: Take 3-year-old fresh bamboo with a breast diameter of 8-12 cm, transport it to the processing workshop within 4 hours after felling, cut it into standard lengths of 1m-1.5m, grind the yellow and green bamboo inside and outside the fresh bamboo, and use high-pressure air washing technology to remove the protruding parts of the bamboo nodes and impurities, and control the impurity residue within 0.3%; then use a blade or laser cutting machine to cut and crush it into 8mm-12mm bamboo aggregate particles;

[0046] Soaking treatment: using vacuum negative pressure assisted soaking technology, the bamboo aggregate particles are transferred to a special soaking cabin with good sealing performance, the vacuum equipment is started, the air pressure in the cabin is uniformly reduced to -0.08MPa to -0.1MPa, and the negative pressure environment is maintained for 30min, so that the internal pores of the bamboo aggregate form microscopic channels that are conducive to the penetration of the protective liquid; then, the soaking liquid is preheated to 30℃-35℃, and the soaking liquid is steadily injected at a flow rate of 0.2m3 / min, so that the bamboo aggregate particles are fully immersed in the soaking liquid, and soaked for 12-15h under normal pressure; after the soaking is completed, gravity is used to drain naturally for 3-4h, and the auxiliary ventilation equipment is adjusted to a wind speed of 0.5-1m / s in combination with the feedback of the humidity sensor in the cabin, and the moisture content of the bamboo aggregate is controlled to be 12%-15%; wherein, the main function of the soaking liquid is to penetrate into the interior of the bamboo aggregate to improve its durability, corrosion resistance, alkali resistance and other properties, and the soaking liquid can be a calcium chloride solution or a silicate solution. In this embodiment, a calcium chloride solution is used;

[0047] Steam treatment: the drained bamboo aggregate particles are transferred into a steam treatment kettle, and the treatment is carried out for 3.5 hours at a temperature of 130°C and a pressure of 0.3 MPa. After the steam treatment is completed, the residual heat is used to assist in drying the bamboo aggregate particles to obtain bamboo aggregate;

[0048] S2, using a continuous pyrolysis furnace, taking fresh bamboo leaves and feeding them into the continuous pyrolysis furnace at a feed speed of 0.4-0.6m / min, preheating the feed air to 70-90°C, pyrolyzing at a temperature of 450-550°C for 2.5h, and using an online infrared spectrometer to monitor the carbonization process of the bamboo leaves and the changes in active ingredients in real time, and after cooling, grinding the bamboo leaf ash to a fineness of 0.09mm to obtain bamboo leaf ash;

[0049] S3, using a high-precision electronic scale (accuracy 0.01%), accurately weigh 25 parts of bamboo aggregate in step S1, 28 parts of P.O42.5 ordinary Portland cement, 8 parts of bamboo leaf ash in step S2, 38 parts of sand (fineness modulus 2.7), 13 parts of water, 0.8 parts of polyhydroxyalkanoate, 1.2 parts of lignin sulfonate, 0.02 parts of rosin resin, and 3.6 parts of silicate according to weight parts;

[0050] First, bamboo aggregate and sand are mixed, stirred at a speed of 25-30 r / min for 2-3 minutes, and stirred evenly to obtain a mixture one; then bamboo leaf ash and cement are added to the mixture one, stirred at a speed of 35-40 r / min for 1-2 minutes, and stirred evenly to obtain a mixture two; finally, water, lignin sulfonate, rosin resin and silicate are added to the mixture two, stirred at a speed of 45-50 r / min for 3-5 minutes, and stirred evenly to obtain bamboo aggregate concrete with uniform color and a slump of 120-180 mm;

[0051] The above bamboo aggregate concrete was injected into 100mm×100mm×100mm and 150mm×150mm×550mm test molds, fully vibrated and compacted, and then placed in a standard curing room for curing; 3 parallel specimens were taken for each group, and the average value was calculated.

[0052] Embodiment 2:

[0053] The preparation of bamboo aggregate concrete includes the following steps:

[0054] S1. Pretreatment: Take 4-year-old fresh bamboo with a breast diameter of 8-12 cm, transport it to the processing workshop within 4 hours after felling, cut it into standard lengths of 1m-1.5m, grind the yellow and green bamboo inside and outside the fresh bamboo, and use high-pressure air washing technology to remove the protruding parts of the bamboo nodes and impurities, and control the impurity residue within 0.3%; then use a blade or laser cutting machine to cut and crush it into 10mm-15mm bamboo aggregate particles;

[0055] Soaking treatment: Vacuum negative pressure assisted soaking technology is used to transfer the bamboo aggregate particles to a special soaking chamber with good sealing performance. The vacuum equipment is started to uniformly reduce the air pressure in the chamber to -0.08MPa to -0.1MPa, and the negative pressure environment is maintained for 30 minutes, so that the internal pores of the bamboo aggregate form microscopic channels that are conducive to the penetration of the protective liquid; then, the soaking liquid is preheated to 30℃-35℃, and the calcium chloride solution is steadily injected at a flow rate of 0.2m3 / min, so that the bamboo aggregate particles are fully immersed in the soaking liquid, and soaked in a normal pressure environment for 12-15h; after the soaking, it is drained naturally by gravity for 3-4h, and the auxiliary ventilation equipment is adjusted in combination with the feedback from the humidity sensor in the chamber, with a wind speed of 0.5-1m / s, to control the moisture content of the bamboo aggregate to 12%-15%;

[0056] Steam treatment: the drained bamboo aggregate particles are transferred into a steam treatment kettle, and the treatment is carried out for 3.5 hours at a temperature of 130°C and a pressure of 0.3 MPa. After the steam treatment is completed, the residual heat is used to assist in drying the bamboo aggregate particles to obtain bamboo aggregate;

[0057] S2, using a continuous pyrolysis furnace, taking fresh bamboo leaves and feeding them into the continuous pyrolysis furnace at a feed speed of 0.4-0.6m / min, preheating the feed air to 70-90°C, pyrolyzing at a temperature of 450-550°C for 2.5h, and using an online infrared spectrometer to monitor the carbonization process of the bamboo leaves and the changes in active ingredients in real time, and after cooling, grinding the bamboo leaf ash to a fineness of 0.1mm to obtain bamboo leaf ash;

[0058] S3, using a high-precision electronic scale (accuracy 0.01%), accurately weigh 33 parts of bamboo aggregate in step S1, 25 parts of P.O42.5 ordinary Portland cement, 6 parts of bamboo leaf ash in step S2, 36 parts of sand (fineness modulus 2.6), 12 parts of water, 0.6 parts of polyhydroxyalkanoate, 1 part of lignin sulfonate, 0.018 parts of rosin resin, and 3.1 parts of silicate according to weight parts;

[0059] First, bamboo aggregate and sand are mixed, stirred at a speed of 25-30 r / min for 2-3 minutes, and stirred evenly to obtain a mixture one; then bamboo leaf ash and cement are added to the mixture one, stirred at a speed of 35-40 r / min for 1-2 minutes, and stirred evenly to obtain a mixture two; finally, water, lignin sulfonate, rosin resin and silicate are added to the mixture two, stirred at a speed of 45-50 r / min for 3-5 minutes, and stirred evenly to obtain bamboo aggregate concrete with uniform color and a slump of 120-180 mm;

[0060] The above bamboo aggregate concrete was injected into 100mm×100mm×100mm and 150mm×150mm×550mm test molds, fully vibrated and compacted, and then placed in a standard curing room for curing; 3 parallel specimens were taken for each group, and the average value was calculated.

[0061] Embodiment 3:

[0062] The preparation of bamboo aggregate concrete includes the following steps:

[0063] S1. Pretreatment: Take 5-year-old fresh bamboo with a breast diameter of 8-12 cm, transport it to the processing workshop within 4 hours after felling, cut it into standard lengths of 1m-1.5m, grind the yellow and green bamboo inside and outside the fresh bamboo, and use high-pressure air washing technology to remove the protruding parts of the bamboo nodes and impurities, and control the impurity residue within 0.3%; then use a blade or laser cutting machine to cut and crush it into 6mm-10mm bamboo aggregate particles;

[0064] Soaking treatment: Vacuum negative pressure assisted soaking technology is used to transfer the bamboo aggregate particles to a special soaking chamber with good sealing performance. The vacuum equipment is started to uniformly reduce the air pressure in the chamber to -0.08MPa to -0.1MPa, and the negative pressure environment is maintained for 30 minutes, so that the internal pores of the bamboo aggregate form microscopic channels that are conducive to the penetration of the protective liquid; then, the soaking liquid is preheated to 30℃-35℃, and the calcium chloride solution is steadily injected at a flow rate of 0.2m3 / min, so that the bamboo aggregate particles are fully immersed in the soaking liquid, and soaked in a normal pressure environment for 12-15h; after the soaking, it is drained naturally by gravity for 3-4h, and the auxiliary ventilation equipment is adjusted in combination with the feedback from the humidity sensor in the chamber, with a wind speed of 0.5-1m / s, to control the moisture content of the bamboo aggregate to 12%-15%;

[0065] Steam treatment: the drained bamboo aggregate particles are transferred into a steam treatment kettle, and the treatment is carried out for 3.5 hours at a temperature of 130°C and a pressure of 0.3 MPa. After the steam treatment is completed, the residual heat is used to assist in drying the bamboo aggregate particles to obtain bamboo aggregate;

[0066] S2, using a continuous pyrolysis furnace, taking fresh bamboo leaves and feeding them into the continuous pyrolysis furnace at a feed speed of 0.4-0.6m / min, preheating the feed air to 70-90°C, pyrolyzing at a temperature of 450-550°C for 2.5h, and using an online infrared spectrometer to monitor the carbonization process of the bamboo leaves and the changes in active ingredients in real time, and after cooling, grinding the bamboo leaf ash to a fineness of 0.11mm to obtain bamboo leaf ash;

[0067] S3, using a high-precision electronic scale (accuracy 0.01%), accurately weigh 28 parts of bamboo aggregate in step S1, 22 parts of P.O42.5 ordinary Portland cement, 7 parts of bamboo leaf ash in step S2, 37 parts of sand (fineness modulus 2.8), 14 parts of water, 1 part of polyhydroxyalkanoate, 0.8 parts of lignin sulfonate, 0.022 parts of rosin resin, and 2.9 parts of silicate according to weight parts;

[0068] First, bamboo aggregate and sand are mixed, stirred at a speed of 25-30 r / min for 2-3 minutes, and stirred evenly to obtain a mixture one; then bamboo leaf ash and cement are added to the mixture one, stirred at a speed of 35-40 r / min for 1-2 minutes, and stirred evenly to obtain a mixture two; finally, water, lignin sulfonate, rosin resin and silicate are added to the mixture two, stirred at a speed of 45-50 r / min for 3-5 minutes, and stirred evenly to obtain bamboo aggregate concrete with uniform color and a slump of 120-180 mm;

[0069] The above bamboo aggregate concrete was injected into 100mm×100mm×100mm and 150mm×150mm×550mm test molds, fully vibrated and compacted, and then placed in a standard curing room for curing; 3 parallel specimens were taken for each group, and the average value was calculated.

[0070] Embodiment 4:

[0071] The preparation of bamboo aggregate concrete includes the following steps:

[0072] S1. Pretreatment: Take 5-year-old fresh bamboo with a breast diameter of 8-12 cm, transport it to the processing workshop within 4 hours after felling, cut it into standard lengths of 1m-1.5m, grind the yellow and green bamboo inside and outside the fresh bamboo, and use high-pressure air washing technology to remove the protruding parts of the bamboo nodes and impurities, and control the impurity residue within 0.3%; then use a blade or laser cutting machine to cut and crush it into 6mm-10mm bamboo aggregate particles;

[0073] Soaking treatment: Vacuum negative pressure assisted soaking technology is used to transfer the bamboo aggregate particles to a special soaking chamber with good sealing performance. The vacuum equipment is started to uniformly reduce the air pressure in the chamber to -0.08MPa to -0.1MPa, and the negative pressure environment is maintained for 30 minutes, so that the internal pores of the bamboo aggregate form microscopic channels that are conducive to the penetration of the protective liquid; then, the soaking liquid is preheated to 30℃-35℃, and the calcium chloride solution is steadily injected at a flow rate of 0.2m3 / min, so that the bamboo aggregate particles are fully immersed in the soaking liquid, and soaked in a normal pressure environment for 12-15h; after the soaking, it is drained naturally by gravity for 3-4h, and the auxiliary ventilation equipment is adjusted in combination with the feedback from the humidity sensor in the chamber, with a wind speed of 0.5-1m / s, to control the moisture content of the bamboo aggregate to 12%-15%;

[0074] Steam treatment: the drained bamboo aggregate particles are transferred into a steam treatment kettle, and the treatment is carried out for 3.5 hours at a temperature of 130°C and a pressure of 0.3 MPa. After the steam treatment is completed, the residual heat is used to assist in drying the bamboo aggregate particles to obtain bamboo aggregate;

[0075] S2, using a continuous pyrolysis furnace, taking fresh bamboo leaves and feeding them into the continuous pyrolysis furnace at a feed speed of 0.4-0.6m / min, preheating the feed air to 70-90°C, pyrolyzing at a temperature of 450-550°C for 2.5h, and using an online infrared spectrometer to monitor the carbonization process of the bamboo leaves and the changes in active ingredients in real time, and after cooling, grinding the bamboo leaf ash to a fineness of 0.11mm to obtain bamboo leaf ash;

[0076] S3, using a high-precision electronic scale (accuracy 0.01%), accurately weigh 28 parts of bamboo aggregate in step S1, 22 parts of P.O42.5 ordinary Portland cement, 7 parts of bamboo leaf ash in step S2, 37 parts of sand (fineness modulus 2.8), 14 parts of water, 1 part of polyhydroxyalkanoate, 0.8 parts of lignin sulfonate, 0.022 parts of rosin resin, 2.9 parts of silicate and 1 part of cupric chloride according to weight parts;

[0077] First, bamboo aggregate and sand are mixed, stirred at a speed of 25-30 r / min for 2-3 minutes, and stirred evenly to obtain a mixture one; then bamboo leaf ash and cement are added to the mixture one, stirred at a speed of 35-40 r / min for 1-2 minutes, and stirred evenly to obtain a mixture two; finally, water, lignin sulfonate, rosin resin, silicate and cupric chloride are added to the mixture two, stirred at a speed of 45-50 r / min for 3-5 minutes, and stirred evenly to obtain bamboo aggregate concrete with uniform color and a slump of 120-180 mm;

[0078] The above bamboo aggregate concrete was injected into 100mm×100mm×100mm and 150mm×150mm×550mm test molds, fully vibrated and compacted, and then placed in a standard curing room for curing; 3 parallel specimens were taken for each group, and the average value was calculated.

[0079] Example 5: Preparation of bamboo aggregate concrete

[0080] S1. Pretreatment: Take 3-year-old fresh bamboo with a breast diameter of 8-12 cm, transport it to the processing workshop within 4 hours after felling, cut it into standard lengths of 1m-1.5m, grind the yellow and green bamboo inside and outside the fresh bamboo, and use high-pressure air washing technology to remove the protruding parts of the bamboo nodes and impurities, and control the impurity residue within 0.3%; then use a blade or laser cutting machine to cut and crush it into 8mm-12mm bamboo aggregate particles;

[0081] Soaking treatment: Vacuum negative pressure assisted soaking technology is used to transfer the bamboo aggregate particles to a special soaking chamber with good sealing performance. The vacuum equipment is started to uniformly reduce the air pressure in the chamber to -0.08MPa to -0.1MPa, and the negative pressure environment is maintained for 30 minutes, so that the internal pores of the bamboo aggregate form microscopic channels that are conducive to the penetration of the protective liquid; then, the soaking liquid is preheated to 30℃-35℃, and the calcium chloride solution is steadily injected at a flow rate of 0.2m3 / min, so that the bamboo aggregate particles are fully immersed in the soaking liquid, and soaked in a normal pressure environment for 12-15h; after the soaking, it is drained naturally by gravity for 3-4h, and the auxiliary ventilation equipment is adjusted in combination with the feedback from the humidity sensor in the chamber, with a wind speed of 0.5-1m / s, to control the moisture content of the bamboo aggregate to 12%-15%;

[0082] Steam treatment: the drained bamboo aggregate particles are transferred into a steam treatment kettle, and the treatment is carried out for 3.5 hours at a temperature of 130°C and a pressure of 0.3 MPa. After the steam treatment is completed, the residual heat is used to assist in drying the bamboo aggregate particles to obtain bamboo aggregate;

[0083] S2, using a high-precision electronic scale (accuracy 0.01%), accurately weigh 28 parts of bamboo aggregate, 28 parts of P.O42.5 ordinary Portland cement, 37 parts of sand (fineness modulus 2.8), 14 parts of water, 0.8 parts of lignin sulfonate, 0.022 parts of rosin resin, and 2.8 parts of silicate in step S1 according to weight parts;

[0084] First, bamboo aggregate and sand are mixed, stirred at a speed of 25-30 r / min for 2-3 minutes, and stirred evenly to obtain a mixture one; then bamboo leaf ash and cement are added to the mixture one, stirred at a speed of 35-40 r / min for 1-2 minutes, and stirred evenly to obtain a mixture two; finally, water, lignin sulfonate, rosin resin and silicate are added to the mixture two, stirred at a speed of 45-50 r / min for 3-5 minutes, and stirred evenly to obtain bamboo aggregate concrete with uniform color and a slump of 120-180 mm;

[0085] The above bamboo aggregate concrete was injected into 100mm×100mm×100mm and 150mm×150mm×550mm test molds, fully vibrated and compacted, and then placed in a standard curing room for curing; 3 parallel specimens were taken for each group, and the average value was calculated.

[0086] Example 6: Preparation of medium density foamed concrete

[0087] S1. Select P.O42.5 ordinary Portland cement that meets national standards and is free of moisture and agglomeration. Select sand with a fineness modulus of about 2.8, sieve to remove impurities and large particles, and ensure that the aggregate particles are uniform. According to the types and instructions of common foaming agents commonly used in the market, dilute the high-performance protein foaming agent with water, stir evenly, and set aside.

[0088] S2. Use high-speed stirring method to put the diluted foaming agent solution into a special foaming machine and stir it at a speed of 1000-1500r / min for 5-10min to make the foaming agent fully foam and form uniform and delicate foam;

[0089] S3. Use a high-precision electronic scale (accuracy 0.01%) to accurately weigh 30 parts of cement, 40 parts of sand, 15 parts of water, 1 part of lignin sulfonate, 0.03 parts of rosin resin, and 2 parts of silicate according to weight; first put the cement and sand into a mixer, stir at a speed of 20-25r / min for 2-3min to make them preliminarily mixed and uniform. Add the weighed water, lignin sulfonate, rosin resin and silicate to the above mixture, stir at a speed of 35-40r / min for 3-5min to fully mix the components to obtain a uniform concrete slurry;

[0090] S4. Slowly add the prepared foam to the concrete slurry, stirring at a speed of 40-45r / min while adding, so that the foam and the concrete slurry are fully mixed, until the slump of the concrete reaches about 120-180mm, forming a medium-density foam concrete with uniform color;

[0091] S5. Pour the mixed medium-density foam concrete into the test molds of 100mm×100mm×100mm and 150mm×150mm×550mm. During the pouring process, it can be vibrated appropriately, but care should be taken to avoid excessive vibration that may cause foam rupture and affect the performance of the concrete. The molds after injection are immediately placed in a standard curing room for curing. The curing temperature is controlled at 20℃-25℃ and the relative humidity is above 90%. Three parallel specimens are made for each group. After curing to the specified age, the average values ​​of performance indicators such as compressive strength are calculated.

[0092] Example 7: Performance Test

[0093] 1. Experimental Materials

[0094] Take the test pieces prepared in Examples 1-6.

[0095] 2. Experimental methods

[0096] The specimens of Examples 1-6 were tested for compression, flexure, splitting and tensile strength. The compressive strength test of bamboo aggregate concrete was carried out according to the requirements of the Standard Test Methods for Physical and Mechanical Properties of Ordinary Concrete (GB / T50081-2019). The loading rate was 0.3MPa / s until the specimen was destroyed; the compressive strength of each group was the average value of the test values ​​of three specimens of 100mm×100mm×100mm as the test result, accurate to 0.1MPa. If the maximum or minimum value of the three test values ​​has a difference of more than 15% from the middle value, the compressive strength of the group of specimens is the middle value. The difference between the maximum and minimum values ​​and the middle value exceeds 15% of the middle value, and this group of results is invalid; according to the requirements of the Standard Test Methods for Physical and Mechanical Properties of Ordinary Concrete (GB / T50081-2019), 3 specimens of 400mm×100mm×100mm were made in each group. The test device is a 100kN testing machine, loaded at a speed of 0.03MPa / s. The fully automatic data acquisition system collects load and deflection data simultaneously. According to the requirements of the Standard for Test Methods of Physical and Mechanical Properties of Ordinary Concrete (GB / T50081-2019), three specimens with a size of 100mm×100mm×100mm were made for each group. The test device is a 100kN testing machine, which is loaded at a speed of 0.03MPa / s.

[0097] 3. Experimental results

[0098] Table 1 Comparison of the performance of concrete in Examples 1-6

[0099] Example Compressive strength(MPa) Flexural strength(MPa) Splitting tensile strength (MPa) 1 16.5 4.9 1.9 2 16.3 5.0 1.7 3 17.1 5.2 2.0 4 17.5 5.9 2.2 5 10.2 4.0 1.4 6 5.0 1.5 0.5

[0100] according to Figure 1 As shown in Table 1, the compressive strength, flexural strength and splitting tensile strength of the bamboo aggregate concrete in the present invention are all improved compared with those of bamboo aggregate concrete, and are significantly better than the mechanical properties of medium-density foam concrete.

[0101] Example 8: Acid-base test

[0102] 1. Experimental Materials

[0103] Take the test pieces prepared in Examples 1-6.

[0104] 2. Experimental methods

[0105] The test pieces of Examples 1-6 were completely immersed in an acid-base solution with a pH value of 4-9 for 30 days to simulate the long-term corrosion of building materials in a weakly acidic to weakly alkaline environment. This acid-base range covers common acid rain environments (pH about 4-5) and slightly alkaline soil and water contact scenarios around some industrial buildings (pH up to 8-9)

[0106] 3. Experimental results

[0107] After the immersion, the specimen of Example 1 showed a slight discoloration in appearance, with a uniform and light color tone, and the integrity of the specimen was good. The mass loss rate was only 1.2% when weighed by a precision electronic balance (accuracy 0.001g), and the mechanical properties remained considerable. The residual compressive strength was measured by a universal material testing machine to be 11.8MPa, and the residual flexural strength reached 4.0MPa. Compared with the initial performance, the compressive strength retention rate was about 94.4%, and the flexural strength retention rate was about 87.0%, showing good acid and alkali corrosion resistance, and the key structure was not significantly damaged, and the internal chemical bonds and microstructural stability of the material were maintained;

[0108] The sample of Example 2 has a slight peeling phenomenon locally on its surface, with the peeling area accounting for less than 5% and the peeling depth being between 0.1-0.2 mm. No through cracks are found, and the density of the internal structure has no significant deterioration. The mass loss rate is calculated to be 1.5%, the remaining compressive strength is 10.9 MPa, with a retention rate of about 92.4%, and the remaining flexural strength is 3.8 MPa, with a retention rate of about 86.4%, indicating that although the material has surface damage under acid and alkali erosion, the core bearing capacity is less affected.

[0109] The mass loss rate of the specimen in Example 3 was determined to be 1.3%, the remaining compressive strength was 10.2 MPa, the retention rate was about 83.6%, and the remaining flexural strength was 3.3 MPa, the retention rate was about 70.2%, and the overall durability still met the requirements of most conventional building scenarios;

[0110] The mass loss rate of the specimen in Example 4 was determined to be 1.1%, the remaining compressive strength was 11.2 MPa, the retention rate was about 90%, the remaining flexural strength was 3.4 MPa, the retention rate was about 71.1%, and the overall durability met the requirements of most conventional building scenarios;

[0111] The mass loss rate of the specimen in Example 5 was determined to be 2.0%, the remaining compressive strength was 7.2 MPa, the retention rate was about 78%, and the remaining flexural strength was 2 MPa, the retention rate was about 70%, indicating that the surface of the material was damaged under acid and alkali erosion, and the core bearing capacity was greatly affected;

[0112] The mass loss rate of the specimen in Example 6 was determined to be 3.1%, the remaining compressive strength was 5.9 MPa, the retention rate was about 62%, and the remaining flexural strength was 1.3 MPa, the retention rate was about 61%;

[0113] Example 9: Wet-dry alternating working condition test

[0114] 1. Experimental Materials

[0115] Take the test pieces prepared in Examples 1-6.

[0116] 2. Experimental methods

[0117] Simulating outdoor damp-dry alternating working conditions, a 12-hour soaking and 12-hour drying cycle was set, with a total of 20 cycles performed, which is close to the actual situation where building materials are affected by tides, precipitation, and sun drying.

[0118] 3. Experimental results

[0119] After the cycle, fine cracks were visible on the surface of the test piece of Example 1, and the crack width was mostly between 0.05-0.1 mm. After quality monitoring, the loss rate was 2%, the remaining compressive strength was 10.5 MPa, the retention rate was about 84.0%, and the remaining flexural strength was 3.7 MPa, the retention rate was about 80.4%, indicating that the material structure can withstand multiple dry-wet alternating impacts, and the internal moisture migration did not cause serious damage;

[0120] The number of cracks in the specimen of Example 2 is slightly more than that in Example 1, with an average of about 3-4 cracks per square centimeter, but the crack depth is shallow. After 24 hours of static observation, there is no expansion trend, and the structural stability is still there. The mass loss rate is 2.3%, the remaining compressive strength is 9.8MPa, the retention rate is about 83.1%, and the remaining flexural strength is 3.4MPa, the retention rate is about 77.3%, reflecting that in the more frequent dry-wet cycles, the material microstructure adjusts and adapts, and no significant damage occurs;

[0121] The crack distribution on the surface of the specimen of Example 3 is relatively uniform, with a spacing of about 3-5mm and an average depth of about 1.5mm. The mass loss rate is 2.1%, the remaining compressive strength is 9.0MPa, the retention rate is about 73.8%, and the remaining flexural strength is 3.0MPa, the retention rate is about 63.8%. The durability of the material has withstood the test, and although the performance has been attenuated to a certain extent, it still has practical value;

[0122] The crack distribution on the surface of the specimen of Example 4 is relatively uniform, with a spacing of about 3-4mm and an average depth of about 1.5mm. The mass loss rate is 1.9%, the remaining compressive strength is 9.1MPa, the retention rate is about 78%, and the remaining flexural strength is 3.2MPa, the retention rate is about 63.8%. The durability of the material has withstood the test and has practical value;

[0123] The specimen of Example 5 has many surface cracks, a mass loss rate of 3.1%, a residual compressive strength of 7.7 MPa, a retention rate of about 68%, and a residual flexural strength of 2.0 MPa, a retention rate of about 59%;

[0124] The specimen of Example 3 has many cracks on its surface; the mass loss rate is 4.2%, the remaining compressive strength is 6.0 MPa, the retention rate is about 60%, and the remaining flexural strength is 1.5 MPa, the retention rate is about 48%.

[0125] Example 10: Freeze-thaw cycle test

[0126] 1. Experimental Materials

[0127] Take the test pieces prepared in Examples 1-6.

[0128] 2. Experimental methods

[0129] In a freeze-thaw cycle environment simulating severe cold regions, the specimens underwent a cycle of freezing at -15°C for 4 hours and thawing at 20°C for 4 hours, for a total of 15 times, to consider the performance evolution of the material under the repeated effects of low-temperature frost heave, ice crystal formation and melting.

[0130] 3. Experimental results

[0131] A small amount of microcracks were generated on the surface of the specimen of Example 1, with a width of 0.03-0.08 mm and a crack length of less than 20 mm; the mass loss rate was 1.8%, the remaining compressive strength was 9.7 MPa, the retention rate was about 77.6%, and the remaining flexural strength was 3.3 MPa, the retention rate was about 71.7%, indicating that the material had good anti-freeze-thaw performance and could effectively buffer ice crystal pressure;

[0132] The microcracks in the specimen of Example 2 are slightly denser than those in Example 1, with an average of about 8-10 cracks per 10 square centimeters. The cracks do not penetrate the specimen, and the internal pore structure has expanded to a certain extent due to freeze-thaw, but it is not connected into a piece. The mass loss rate is 2.1%, the remaining compressive strength is 9.0MPa, the retention rate is about 76.3%, and the remaining flexural strength is 3.1MPa, the retention rate is about 70.5%, indicating that the material is damaged under the impact of freeze-thaw cycles but maintains the basic load-bearing framework;

[0133] The cracks of the specimen in Example 3 are slightly wider, with the widest part reaching 0.12 mm, but there is no sign of fracture, and the overall structure is intact; the mass loss rate is 1.9%, the remaining compressive strength is 8.5 MPa, the retention rate is about 69.7%, and the remaining flexural strength is 2.8 MPa, the retention rate is about 59.6%. The material still has considerable residual strength after multiple freeze-thaw cycles, and is suitable for low-frequency extreme low-temperature construction projects;

[0134] The cracks of the specimen in Example 4 are slightly wider, with the widest part reaching 0.10 mm, but there is no sign of fracture, and the overall structure is intact; the mass loss rate is 1.8%, the remaining compressive strength is 8.5 MPa, the retention rate is about 70.0%, and the remaining flexural strength is 2.9 MPa, the retention rate is about 60.0%. The material still has considerable residual strength after multiple freeze-thaw cycles, and is suitable for low-frequency extreme low-temperature construction projects;

[0135] The crack width of the specimen in Example 5 is 2.8%, the mass loss rate is 2.8%, the remaining compressive strength is 5 MPa, the retention rate is about 56.1%, and the remaining flexural strength is 1.2 MPa, the retention rate is about 48.2%;

[0136] Example 6 specimen crack width; mass loss rate 4.0%, residual compressive strength 2MPa, retention rate of about 32%, residual flexural strength 0.9MPa, retention rate of about 30.0%;

[0137] The serial numbers of the embodiments of the present application are for description only and do not represent the advantages and disadvantages of the embodiments. The above are only preferred embodiments of the present application, and do not limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made by using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A bamboo aggregate concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 20-30 parts of bamboo aggregate, 20-30 parts of cement, 5-10 parts of bamboo leaf ash, 35-40 parts of sand, 10-15 parts of water, 0.5-1.5 parts of water reducing agent, 0.01-0.03 parts of air entraining agent, 2.5-4.0 parts of coagulant, 0.2-1.2 parts of filler and 0-1.5 parts of chloride ion resistance additive.

2. The bamboo aggregate concrete according to claim 1, characterized in that: The filler is one or more of polyhydroxyalkanoate, ground slag powder and silica fume.

3. The bamboo aggregate concrete according to claim 1, characterized in that: The anti-chloride ion additive is one or more of potassium chloride, sodium potassium chloride and copper chloride.

4. A method for preparing bamboo aggregate concrete according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Preparation of bamboo aggregate: fresh bamboo is cut into standard lengths, impurities are removed, and the bamboo aggregate particles are crushed. The bamboo aggregate particles are first soaked by vacuum negative pressure assisted soaking technology, drained, and then the drained bamboo aggregate particles are steamed by a steam treatment kettle, and dried to obtain bamboo aggregate; S2. Preparation of bamboo leaf ash: pyrolysis, cooling and grinding of fresh bamboo leaves to obtain bamboo leaf ash; S3, first take the bamboo aggregate prepared in step S1 and sand, mix them, stir them evenly, and obtain mixture one; then take the bamboo leaf ash and cement prepared in step S2, add them to mixture one, stir them evenly, and obtain mixture two; finally, take water, water reducing agent, air entraining agent, coagulant, filler and anti-chloride ion additive and add them to mixture two, stir them evenly, and obtain bamboo aggregate concrete.

5. The method for preparing bamboo aggregate concrete according to claim 4, characterized in that: In step S1, the fresh bamboo is 3-5 years old and has a breast diameter of 8-12 cm; the standard length is 1 m-1.5 m; and the particle size of the bamboo aggregate particles is 5 mm-20 mm.

6. The method for preparing bamboo aggregate concrete according to claim 4, characterized in that: The specific steps of soaking the bamboo aggregate particles using the vacuum negative pressure assisted soaking technology in step S1 are as follows: The crushed bamboo aggregate particles are first treated in a negative pressure environment for 30 minutes, and then soaked in a normal pressure environment for 12-15 hours.

7. The method for preparing bamboo aggregate concrete according to claim 6, characterized in that: The negative pressure is -0.08 MPa to -0.1 MPa.

8. The method for preparing bamboo aggregate concrete according to claim 4, characterized in that: The steam treatment in step S1 is performed under a pressure of 0.3 MPa, a temperature of 130° C., and a time of 3.5 h; the moisture content of the bamboo aggregate is 12%-15%.

9. The method for preparing bamboo aggregate concrete according to claim 4, characterized in that: The pyrolysis temperature in step S2 is 400-600° C., and the pyrolysis time is 2-3 hours; the grinding fineness of the bamboo leaf ash is 0.08-0.12 mm.

10. The method for preparing bamboo aggregate concrete according to claim 4, characterized in that: In step S3, the stirring speed of the mixture 1 is 25-30 r / min, and the stirring time is 2-3 min; the stirring speed of the mixture 2 is 35-40 r / min, and the stirring time is 1-2 min; the stirring speed of the mixture 3 is 45-50 r / min, and the stirring time is 3-5 min.